Peran Fintech Syari’ah Untuk Pemulihan Ekonomi Masa Pandemi Covid-19 (UMKM di Indonesia) - Novita Wulandari; Annisa Mangole (Lembaga Penelitian dan Pengembangan Masyarakat IAINU Kebumen, 2021)
The impact of the Covid-19 outbreak has slowed down some business activities. Other institutions are needed that can support the development of MSMEs in the midst of the Covid-19 outbreak, one of which is sharia fintech. This paper aims to describe alternative funding using Islamic Financial Technology (Fintech) for the recovery of MSMEs affected by the Covid-19 Pandemic in Indonesia. The method used in this research is descriptive analysis with a qualitative approach where this approach explains research on a subject. Data sources are secondary data obtained through library research in the form of journals, news articles, and books related to research. The data that has been collected will be classified, then verified whether it is in accordance with the research and then analyzed. The results of the study found that during the Covid-19 Pandemic the turnover of MSMEs decreased and many MSMEs did not have business capital reserves. PT. Ammana can be a solution for community capital, especially MSMEs and Fintech, which can help improve the effectiveness of government financing assistance and as a parameter that shows an increase in public financial literacy, especially MSMEs in accessing financing and financial transactions.